2019
DOI: 10.21608/zjar.2019.65077
|View full text |Cite
|
Sign up to set email alerts
|

NEW RECORD OF ENTOMOPATHOGENIC BACTERIA, Bacillus aryabhattai STRAIN B8W 22, ISOLATED FROM Cassida vittata Vill. AND ITS PATHOGENICITY AGAINST THIS INSECT IN EGYPTIAN SUGAR BEET FIELDS

Abstract: Cassida vittata Vill. (Coleoptera : Chrysomelidae) is a very important insect pest to sugar beet crop. Its larvae and adults feed upon sugar beet leaves causing significant defoliation, consequently reduce root weight and sugar percent (%) to this crop. Entomopathogenic microorganisms, mainly entomopathogenic bacteria, is a vital factor of the natural mortality against insects. Research on microbial pathogens of insects is increasing to find out environmental friendly alternatives to hazardous chemical insecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…(Coleoptera: Chrysomelidae) is one of the most devastating insects in sugar beet fields, especially the second (mid-September) and third (mid-October) (El-Dessouki, 2019). The larvae and adults of this insect feed upon sugar beet leaves causing reduction in sugar content and sugar root yield by 40.10 and 56.20%, respectively (Bazazo and Besheit, 2019). Many authors showed the importance of this insect pest on sugar beet crops since 1982 -until now e.g., Bassyouny and Beleih (1996) reported that the initial rate of infestation of C. vittata appeared on sugar beet plants late in December or on mid -January for all plantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Coleoptera: Chrysomelidae) is one of the most devastating insects in sugar beet fields, especially the second (mid-September) and third (mid-October) (El-Dessouki, 2019). The larvae and adults of this insect feed upon sugar beet leaves causing reduction in sugar content and sugar root yield by 40.10 and 56.20%, respectively (Bazazo and Besheit, 2019). Many authors showed the importance of this insect pest on sugar beet crops since 1982 -until now e.g., Bassyouny and Beleih (1996) reported that the initial rate of infestation of C. vittata appeared on sugar beet plants late in December or on mid -January for all plantation.…”
Section: Introductionmentioning
confidence: 99%
“…Sheppard et al (2013) clarified that Bacillus thuriengiensis produces crystalline proteins during its stationary phase of growth which are lethal to Lepidoptera, Coleoptera and Diptera insects. Moreover, Bazazo et al (2015) and ( 2016) isolated a new strain of B. thuriengiensis from Pegomyia mixta Vill. and Scrobipalpa ocellatella Boyd larvae, as a first record in Egyptian sugar beet fields.…”
Section: Introductionmentioning
confidence: 99%